Taxonomic Re-Investigation and Geochemical Characterization of Reid's (1974) Species of Spiniferites from Holotype and Topotype Material. (20th December 2018) - Gurdebeke, Pieter R.; Mertens, Kenneth Neil; Bogus, Kara; Marret, Fabienne; Chomérat, Nicolas; Vrielinck, Henk; Louwye, Stephen
Abstract: The genus Spiniferites currently encompasses 142 dinoflagellate cyst species. Some Spiniferites species are difficult to identify because of an incomplete or doubtful description, and/or substandard iconography. This study re-describes and re-illustrates the Spiniferites holotypes first described by Reid in1974 . It also discusses topotype material from surface sediments recovered from British estuaries, and attempts to provide further constraints on the classification of species in this genus using the geochemical characterization of their cyst walls. Reid described four new Spiniferites species: Spiniferites belerius, Spiniferites delicatus, Spiniferites elongatus and Spiniferites lazus . New photomicrographs are presented here for the holotypes of Spiniferites delicatus and Spiniferites elongatus, and additional morphological observations based on newly processed topotype material are given. The geochemical characterization of the Spiniferites cyst walls showed overall consistency with a carbohydrate-based dinosporin. However, variability in the dinosporins suggests that, in this genus, the cyst wall composition may be species-specific. Analysis of the characteristic spectral regions for unclassified Spiniferites species showed that, in some cases, it may be possible to constrain the likely species affinity using the cyst wall chemistry. However, in most cases, the morphologically unspeciated cysts did not show sufficient similarity to an identified species' cyst wall chemistry to be more conclusive. This could either reflect an intermediate species that cannot be clearly characterized using morphology or dinosporin composition, or it represents a completely different species. In either case, both the morphological and geochemical evaluations highlight the difficulties in classifying species of this genus unequivocally.